PENGARUH GIRO WAJIB MINIMUM (GWM), SUKU BUNGA DEPOSITO BERJANGKA, DANA PIHAK KETIGA (DPK) DAN COST OF LOANABLE FUNDS TERHADAP BASE LENDING RATE (BLR) (Studi Pada Bank Swasta Nasional dan Bank Persero yang Terdaftar di Bursa Efek Indonesia Periode 2010-201 - Nabilah, Hashifah; Mawardi, Wisnu (Diponegoro Journal of Management, 2016)
Base lending rate is the implementation process of the management of bank funding. In banking industry which more competitive, banks are required to offer a low base lending rate. On the other hand, the banks had no motivation to maximize revenue. This study is aimed to analyze the effect of reserve requirements, deposit interest rates, third party funds and cost of loanable funds to the base lending rate.            The samples used in this study are 14 private national banks and state-owned banks listed on the Indonesia Stock Exchange in 2010-2014. The method of this research is using multiple regression model with IBM SPSS Statistics 22 program to analyze the effect of independent variables to the dependent variable.            The result shows that the deposit interest rate and the cost of the loanable funds have positive and significant effect to the base lending rate. However, reserve requirements and third party funds does not affect to base lending rate. These results proved that high interest rates on time deposits are the bank's strategy to increase market share of time deposits which is bank's largest sources of funding and the component that has the biggest influence on BLR is COLF amounted to 33.79% of the components that form BLR.